The Role of Social Relations in the Development of the Land Bhakti Youth Organization: An Analysis of Interaction and Familiarity of Members - Maskuri, Abdan; Prasetyo, Muhammad Ryan; Fauziah, Kholifatul (Civil Officium: Journal of Empirical Studies on Social Science, 2024)
This research aims to observe and explore how the relationship that occurs between members of Karang Taruna Bhakti Petanahan in Petanahan Village, Petanahan Sub-district, Kebumen Regency.  Research using descriptive qualitative research method approach. Data collection technique is observation, interviews, documentation, and literature studies. Data validity used source triangulation technique. Data analysis using Miles and Huberman analysis model, is data collection, data reduction, data presentation and data verification. The results of the study show several findings that the interactions that occur between members of Karang Taruna Bhakti Petanahan cannot be separated from the long-standing close relationship. From this familiarity then gave rise to a very long and continuous relationship in maintaining the integrity of program planning within Karang Taruna Bhakti Petanahan.